The Digital Platform Promotion Strategy To Support UMKM In Bangka Belitung Province - Hengki Hengki; Bambang Adiwinoto; Sarwindah; Jonari Pandia; Rismar Yanti (International Journal Of Community Service, 2021)
Since the COVID-19 pandemic entered Indonesia in early March 2020, theeconomy had stopped, thus affecting the socio-economic life of the community.With the pandemic, people's lives are mostly done at home (Work from Home)so that the use of digital platform technology in helping companies work on alarge and small scale, especially in small and medium enterprises in the startupworld. In the promotion strategy by utilizing it is also necessary to use a businessintelligence model which is an analytical tool in the form of business informationthat is used to consolidate, analyze, store and access a lot of data in the contextof business processes that lead to making decisions and actions with the aim ofimproving the performance of business or business strategies in the future.UMKM, especially in the province of Bangka Belitung. Therefore, we intend tocarry out service in educating the public with the theme "digital platformpromotion strategy to support UMKM in Bangka Belitung Province" which aimsto review the use of digital platform technology and the benefits of BusinessIntelligence in the digital business era.